FORE! An Analysis of CEO Shirking - Biggerstaff, Lee; Cicero, David C.; Puckett, Andy (Management Science, 2017)
Using golf play as a measure of leisure, we provide direct evidence that some CEOs shirk their responsibilities to the detriment of firm shareholders. CEOs with lower equity-based incentives play more golf and those that golf the most are associated with firms that have lower operating performance and firm values. Numerous tests accounting for the possible endogenous nature of these relations support a conclusion that CEO shirking causes lower firm performance. New CEOs and those at firms with more independent boards are more likely to be replaced when they shirk, but those with long tenures or less independent boards appear to avoid discipline. This paper was accepted by Lauren Cohen, finance.